Uma abordagem de ensino-aprendizagem de programa??o na educa??o superior - Santana, Bianca Leite (2018)
The proposed approach combines the use of the Scratch environment in a context of game creation, the Python programming language associated with the turtle graphics library, and image manipulation with the Jython Environment for Students (JES). We conducted two exploratory case studies with Civil Engineering students attending a CS1 course at our institution to analyze the impact of this approach on student motivation and learning. Our results describe the motivation present during the course in terms of the Attention, Relevance, Confidence and Satisfaction (ARCS) model, and identify the practical factors that may contribute to increase or decrease student motivation. We also present a framework that shows the positive and negative impacts of the elements of our approach on each of the categories of the ARCS model. Various such elements are common in several teaching-learning situations. From a learning point of view, our findings also show that contextualized and spiral learning has enhanced the learning of concepts such as loops and functions. Scratch facilitates the learning of programming logic, select and repeat structures. Python with Turtle enhances learning of these same concepts with the addition of functions. Finally, the media computation approach has shown potential for learning the concepts of functions and arrays. We believe that the practical factors presented in this work can support the design of CS1 courses for non-majors